Anti-inflammatory and Wound Healing Activity of Gymnospermous Plant Cycas revoluta - Srivastava, Swati; Sharma, Divya Rani; Srivastava, Arvind Kumar; Mukerjee, Alok; Tripathi, Abhishek Kumar; Singh, Sunil Kumar (Indian Journal of Natural Products, 2022)
Background: Wounds are a serious worldwide health problem that place significant economic, financial, and social strain on health care organizations, professionals, patients, and their families. Aim: To investigate the anti- inflammatory and wound healing activity of ethanolic extract of leaves Cycas revoluta. Materials and Methods: In albino rats, the anti- inflammatory and wound healing activity was explored using complete excision, incision wound model and paw edema induced wound model. The wound healing and anti-inflammatory activity were then compared to that of other standard medications available. Results: In both models investigated, different dosages of CREE (200 mg/kg and 400 mg/kg) significantly improved wound healing activity. When compared to the control group of mice, animals treated with CREE had a higher rate of wound contraction (p<0.001), a shorter period for epithelialization (p<0.01), a higher skin breaking strength (p<0.001), and a higher hydroxyproline content. In addition, histopathological investigations of the CREE-treated groups demonstrated better wound healing. Conclusion: The study reveals the wound healing and anti-inflammatory activity of ethanolic extracts (95%) of leaves part of Cycas revoluta in complete wound healing and anti-inflammation model. The extracts seem promising for the development of phytomedicine for wound healing and anti-inflammatory and study provides future research in screening the extract constituents responsible for the wound healing and anti-inflammatory activity
Keywords: Cycas revoluta; Wound healing; Anti-inflammatory; Ethanolic extract (95%)